2005
DOI: 10.1073/pnas.0505758102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the tumor inhibitory triterpenoid avicin G on cell integrity, cytokinesis, and protein ubiquitination in fission yeast

Abstract: Avicins comprise a class of triterpenoid compounds that exhibit tumor inhibitory activity. Here we show that avicin G is inhibitory to growth of the fission yeast Schizosaccharomyces pombe. S. pombe cells treated with a lethal concentration of avicin G (20 M) exhibited a shrunken morphology, indicating that avicin G adversely affects cell integrity. Cells treated with a sublethal concentration of avicin G (6.5 M) exhibited a strong cytokinesis-defective phenotype (multiseptated cells), as well as cell morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Indeed, avicin D-mediated cell death has been reported to be associated with the activation of the death receptor-caspase-8 pathway. 35 Avicins appear also to affect phospholipid-dependent processes, 36 pathway. 35 Moreover, it has recently been shown that some avicins may increase the level of ubiquitinated proteins in human Jurkat T cells possibly through an up-regulation of ubiquitin ligase activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, avicin D-mediated cell death has been reported to be associated with the activation of the death receptor-caspase-8 pathway. 35 Avicins appear also to affect phospholipid-dependent processes, 36 pathway. 35 Moreover, it has recently been shown that some avicins may increase the level of ubiquitinated proteins in human Jurkat T cells possibly through an up-regulation of ubiquitin ligase activity.…”
Section: Resultsmentioning
confidence: 99%
“…35 Moreover, it has recently been shown that some avicins may increase the level of ubiquitinated proteins in human Jurkat T cells possibly through an up-regulation of ubiquitin ligase activity. 36 However, avicins seem to have other, and yet only partially identified, molecular targets. 37 Lebbeckosides A-B, two new avicin analogs isolated from Albizia lebbeck, might therefore be highly useful to further decipher the mechanism of action of this triterpene saponin and obtain new structure-activity relationship data.…”
Section: Resultsmentioning
confidence: 99%
“…Avicin G used at 0.02 mg ml -1 has been shown to be sufficient to inhibit Schizosaccharomyces pombe growth and induce a strong cytokinesisdefective phenotype (multiseptated cells) as well as a shrunken cellular morphology (Gutterman et al 2005). In a wider study Miyakoshi et al (2000) have described how Yucca schidigera steroidal saponins were effective against a wide range of wild S. cerevisiae but also other dermatophytic, food-deteriorating and film-foaming yeast species that spoil soy sauce.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported mitochondrial perturbation, chemoprevention, and inhibition of nuclear factor κB, concluding that triterpenoid saponins from A. victoriae have potential as novel anticancer agents. [37][38][39][40][41][42] Furthermore, autophagy-induced cell death which could be regulated by treatment with chloroquine was also tested, and it was concluded that avicin D-induced autophagic cell death can be abrogated by knockdown of tuberous sclerosis complex 2, which is a key mediator linking AMP-activated protein kinase, and mammalian target of rapamycin (mTOR). This validated autophagic cell death in the presence of avicins.…”
Section: Cytotoxic Saponins In Preclinical and Clinical Settingsmentioning
confidence: 99%